Low liquor dyeing of cotton fabric with reactive dye by an eco-friendly technique. (1st October 2018) - Irfan, Mohammad; Zhang, Hongjuan; Syed, Uzma; Hou, Aiqin
Abstract: Generally the exhaust dyeing process utilizes a large amount of energy, time and high liquor ratio. On the contrary, the microwave irradiation can be used for the exhaust dyeing that consumes less energy and less time. In this research, the environmental friendly technique, the microwave irradiation, is used to dye cotton fabric at lower liquor ratio through the exhaust dyeing process and it is compared with the conventional dyeing method. The exhaustion percentage, fixation percentage, and color strength values have been measured and a suitable recipe is obtained. It is found that the microwave technique facilitates the process by minimizing the dyeing time and maximizing the exhaustion percentage, fixation percentage, and color strength values. Furthermore, the microwave technique is considered as a green technique and higher exhaustion and fixation percentages indicate that there is comparatively less residue dye in the effluent. XRD and SEM tests also performed to analyze whether the microwave has affected the morphological structure but from the results, there is not a considerable difference observed. Finally, the colorfastness tests have been carried out and compared with the conventionally dyed samples and the results are almost the same for both techniques. Hence the microwave technique is providing almost the same quality product by using less time with the environment friendliness. Highlights: The microwave irradiation is used to dye cotton fabric at lower liquor ratio. The microwave technique is providing the same quality product by less time. It has potential application in cleaner production of cotton fabric dyeing.